THE USE OF LIVEWORKSHEETS (LWS) FOR VOCABULARY LEARNING - Zeiniaty Rafaelly Sabaru; Mister G. Maru; Merlin Maukar (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2023)
In Indonesia, English is considered the first foreign language taught from high school to university. Vocabulary is very important to students, which is why researchers want to know about techniques that can be used to increase students' vocabulary. This study deals with vocabulary teaching techniques and aims to find out if using Liveworksheets can improve English vocabulary of 7th grade students at SMP Negri 5 Tondano school. This study is a quantitative study through pre-experimental design with group pre-test and post-test design with 11 students. The results of this study indicate that students' English vocabulary increased significantly after using Liveworksheets in vocabulary lessons. This is evidenced by the average score of the test before and after the test, i.e., 3.54 before the test and 8.0 after the test. This means that Liveworksheets are effective in increasing the English vocabulary of students from grade VII to SMP Negeri 5 Tondano. Live spreadsheets are easy to use, can be viewed for free via the web, used anytime, anywhere, have the effect of motivating students to learn and are a new teaching method. Use a laptop or smartphone to access Liveworksheets. And new learning techniques can focus students' attention on learning.